Surface Roughness Analysis in Turning of AISI 1045 Steel with Anova and Scheffe Test - Am. Mufarrih; Hesti Istiqlaliyah; Mohammad Zaenal Fanani (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2018)
Turning process is a very important machining process in the manufacturing industry. The quality characteristics of a turning machining product can be seen from the level of surface roughness carried out in the turning process. The purpose of this study was to determine the effect of spindle speed, feeding and the main cutting angle on surface roughness. Surface roughness measurement using a surftest SJ-301. The material used in this study is AISI 1045 steel. While analysis of variance (ANOVA) is used to process data. The results showed that the lowest surface roughness can be achieved at spindle speed of 765 rpm, feeding of 0.15 mm / rev and main cutting angle of 85. Data analysis explained that the spindle speed, feeding and main cutting angle had a significant effect on surface roughness. Increased spindle speed, feeding and main cutting angle will reduce surface roughness. The scheffe test results also show contrasting results between the variables studied.